2010
DOI: 10.1007/s11064-010-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Primary and Secondary Cultures of Astrocytes Prepared from Mouse Cerebral Cortex

Abstract: Astrocyte cultures were prepared from cerebral cortex of new-born and 7-day-old mice and additionally, the cultures from new-born animals were passaged as secondary cultures. The cultures were characterized by immunostaining for the astrocyte markers glutamine synthetase (GS), glial fibrillary acidic protein, and the glutamate transporters EAAT1 and EAAT2. The cultures prepared from 7-day-old animals were additionally characterized metabolically using (13)C-labeled glucose and glutamate as well as (15)N-labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In this study we measured the stoichiomentry of CO 2 produced from transported glutamate. Previous studies using astrocytes (Farinelli and Nicklas, 1992; McKenna et al, 1996; Rao and Murthy, 1993; Skytt et al, 2010; Sonnewald et al, 1997; Waniewski and Martin, 1986; Yu et al, 1982), synaptosomes (Yudkoff et al, 1994), and brain slices (El Hage et al, 2011) have examined the catabolism of glutamate and its conversion to CO 2 with conflicting results. Some studies found a relatively small portion of glutamate flux through the tricarboxylic acid (TCA) cycle, whereas others found a large portion of glutamate entering the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we measured the stoichiomentry of CO 2 produced from transported glutamate. Previous studies using astrocytes (Farinelli and Nicklas, 1992; McKenna et al, 1996; Rao and Murthy, 1993; Skytt et al, 2010; Sonnewald et al, 1997; Waniewski and Martin, 1986; Yu et al, 1982), synaptosomes (Yudkoff et al, 1994), and brain slices (El Hage et al, 2011) have examined the catabolism of glutamate and its conversion to CO 2 with conflicting results. Some studies found a relatively small portion of glutamate flux through the tricarboxylic acid (TCA) cycle, whereas others found a large portion of glutamate entering the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Primary astrocytes were prepared from neonatal (<24-hours old) SJL/J mouse brains using methods similar to those described previously [16,17]. Primary glial cell cultures were maintained in (D)MEM (Gibco, Carlsbad, CA, USA) supplemented with 10% FCS, 6 mg/ml glucose, and 5 μg/ml bovine pancreas insulin (Sigma-Aldrich, St. Louis, MO, USA), referred to as complete medium, in 10% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Neuronal stem cells tend to be confined to the periventricular area, thus this is not a major issue for preparation of astrocytes from other brain regions. In view of the above, investigations of GFAP expression can be supplemented with other astrocyte-specific markers such as GS (20), pyruvate carboxylase (PC) (24, 25), excitatory amino acid transporter 2 (GLT-1) (26) or aldehyde dehydrogenase 1 family member L1 (Aldh1L1)(6). …”
Section: The Use Of Primary Astrocyte Culturesmentioning
confidence: 99%